A novel partial SOI EDMOS (>800 V) with a buried N-type layer on the double step buried oxide. (March 2015) - Wang, Qian; Cheng, Xinhong; Wang, Zhongjian; Xia, Chao; Shen, Lingyan; Zheng, Li; Cao, Duo; Yu, Yuehui; Shen, DaShen
Highlights: Partial silicon-on-insulator extended drain MOSFET is proposed. Two new electric field peaks are introduced by the double step BOX layer. The electric field in the BOX layer is enhanced by the buried N-type layer. The proposed structure improves the breakdown voltage. Self-heating effect is suppressed in the proposed structure. Abstract: In this paper, a high voltage partial silicon-on-insulator (PSOI) extended drain metal–oxide–semiconductor (EDMOS) field effect transistor with a buried N-type layer (BNL) on the double-step buried oxide (DSBOX) is proposed. Due to the DSBOX, two additional peaks of the electric field are introduced in the drift region, modulating the electric field, achieving a more uniform distribution in the drift, and improving the lateral breakdown voltage (BV). The BNL provides a great population of positive charges on top of the DSBOX and enhances the electric field in the BOX, leading to a higher vertical BV. Moreover, the silicon window provides a thermal conduction path from the active region to the substrate, significantly alleviating the self-heating effect (SHE) in comparison to the conventional SOI-EDMOS (C-SOI).